KAT8 catalyzes the acetylation of SEPP1 at lysine 247/249 and modulates the activity of CD8+ T cells via LRP8 to promote anti-tumor immunity in pancreatic cancer - Zhongfei Zhu; Gang Nie; Xiaobo Peng; Xianbao Zhan; Dan Ding (Cell & Bioscience)
Abstract Background Pancreatic cancer (PC) remains one of the most lethal malignancies with unfavorable prognosis globally. Bioinformatics analysis predicted that SEPP1 was low expressed in PC and related to tumor immune microenvironment, but its biological function was still unclear. Methods PC xenograft and liver metastasis mouse models, as well as PC cell-MDSCs co-culture system, were established for in vivo and in vitro studies, respectively. The expression and localization of key molecules were detected by qRT-PCR, western blot, immunohistochemistry and immunofluorescence. Flow cytometry was employed to assess the abundance of immune cells and cell apoptosis. The interactions among KAT8, SEPP1 and LRP8 were detected by co-IP. Cell viability, migration and invasion were monitored by CCK-8 and transwell assays. Results SEPP1 was downregulated in pancreatic tumors, and it was positively correlated with the abundance of CD8+ T cells. In vivo overexpression of SEPP1 impaired PC tumor growth and liver metastasis via modulating the abundance of CD8+ T cell and MDSCs. KAT8 upregulated SEPP1 transcription and protein level via catalyzing the acetylation at K247/249 on SEPP1, and SEPP1 impaired MDSCs survival via its receptor LRP8, thus regulating CD8+ T cell-mediated immune responses in PC. In vivo studies further revealed that SEPP1 recombinant protein enhanced the efficacy of anti-PD-1 therapy in PC xenograft mouse model. Conclusion KAT8 catalyzed the acetylation of SEPP1 at K247/249 and modulated the activity of CD8+ T cells via LRP8 to promote anti-tumor immunity in PC.